Perceptual Characterization of the Macronutrient Picture System (MaPS) for Food Image fMRI - King, Jill L.; Fearnbach, S. Nicole; Ramakrishnapillai, Sreekrishna; Shankpal, Preetham; Geiselman, Paula J.; Martin, Corby K.; Murray, Kori B.; Hicks, Jason L.; McClernon, F. Joseph; Apolzan, John W.; Carmichael, Owen T. (Frontiers in Psychology, 2018)
Food image fMRI paradigms are used widely for investigating the neural basis of ingestive behavior. However, these paradigms have not been validated in terms of ingestive behavior constructs, engagement of food-relevant neural systems, or test-retest reliability, making the generalizability of study findings unclear. Therefore, we validated the Macronutrient Picture System (MaPS)1, which includes food images from the six categories represented in the Geiselman Food Preference Questionnaire (FPQ)2. Twenty-five healthy young adults (n=21 female, mean age = 20.6 ± 1.1 years, mean BMI = 22.1 ± 1.9 kg/m2) rated the MaPS images in terms of visual interest, appetitive quality, nutrition, emotional valence, liking, and frequency of consumption, and completed the FPQ. In a second study, a separate sample of 12 individuals (n=8 female, mean age = 25.0 ± 6.5 years, mean BMI = 28.2 ± 8.7 kg/m2) viewed MaPS and control images (vegetables and non-food) during two separate 3T BOLD fMRI scans after fasting overnight. Intuitively, high fat/high sugar (HF/HS) and high fat/high complex carbohydrate (HF/HCCHO) images achieved higher liking and appetitive ratings, and lower nutrition ratings, than low fat/low complex carbohydrate/high protein (LF/LCHO/HP) images on average. Within each food category, FPQ scores correlated strongly with MaPS image liking ratings (p<0.001). Brain activation differences between viewing images of HF/HS and vegetables, and between HF/HCCHO and vegetables, were seen in several reward-related brain regions (e.g., putamen, insula, and medial frontal gyrus). Intra-individual, inter-scan agreement in a summary measure of brain activation differences in seven reward network regions of interest was high (ICC=0.61), and was even higher when two distinct sets of food images with matching visual ratings were shown in the two scans (ICC=0.74). These results suggest that the MaPS provides valid representation of food categories and reliably activates food-reward-relevant neural systems.